2016
DOI: 10.2169/internalmedicine.55.7293
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Extracellular Signal-regulated Kinase 5 and Ankyrin Repeat Domain 1 in Composite Pheochromocytoma and Ganglioneuroblastoma Detected Incidentally in the Adult Adrenal Gland

Abstract: Composite pheochromocytoma (cPC) is extremely rare, arising in the adrenal medulla as a mixture of PC and other tumors of neural origin. We herein report on a case of adrenal incidentaloma post-operatively diagnosed as cPC with ganglioneuroblastoma (GNBL). The PC component had 7 points on the PASS, a Ki-67 index of 5.1%, a focal absence of sustentacular cells, and no genetic aberrations in succinate dehydrogenase subunit B. The GNBL component exhibited no N-myc amplification. Tumor cells of both components wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…In total, 50 published studies were identified by the PubMed search engine when employing the term “PASS pheochromocytoma”. After an initial assessment of eligibility, including the presence of a PASS stratified pheochromocytoma cohort as well as an exclusion of irrelevant studies and reviews, 28 original studies and case reports were initially included in the review [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. After careful revision of each study, eight additional studies were disqualified from inclusion based on the failure to meet our fourth inclusion criterion of “clearly identified subgroup information (number of tumor samples with and/or without evidence of synchronous or metachronous evidence of malignancy respectively, with the associated PASS score clearly identifiable)” [5,6,8,9,13,14,18,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 50 published studies were identified by the PubMed search engine when employing the term “PASS pheochromocytoma”. After an initial assessment of eligibility, including the presence of a PASS stratified pheochromocytoma cohort as well as an exclusion of irrelevant studies and reviews, 28 original studies and case reports were initially included in the review [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. After careful revision of each study, eight additional studies were disqualified from inclusion based on the failure to meet our fourth inclusion criterion of “clearly identified subgroup information (number of tumor samples with and/or without evidence of synchronous or metachronous evidence of malignancy respectively, with the associated PASS score clearly identifiable)” [5,6,8,9,13,14,18,28].…”
Section: Resultsmentioning
confidence: 99%
“…After careful revision of each study, eight additional studies were disqualified from inclusion based on the failure to meet our fourth inclusion criterion of “clearly identified subgroup information (number of tumor samples with and/or without evidence of synchronous or metachronous evidence of malignancy respectively, with the associated PASS score clearly identifiable)” [5,6,8,9,13,14,18,28]. Therefore, a total of 20 studies were included in the meta-analysis [1,3,4,7,10,11,12,15,16,17,19,20,21,22,23,24,25,26,27,29]. These studies and the associated outcomes are detailed in Table 1 and illustrated in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation